PATHOPHYSIOLOGY OF THE LUNGS AND RELATED DISEASES - Temirova Dilnoza Valiyevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract:The lungs are essential for gas exchange and play a crucial role in maintaining oxygenation and acid-base balance in the body. Pathophysiological changes in lung tissue, airways, and pulmonary circulation can lead to various respiratory diseases, including chronic obstructive pulmonary disease (COPD), asthma, pulmonary fibrosis, and lung infections. This article explores the mechanisms underlying lung pathophysiology and the impact of these diseases on respiratory function.